Examining the effects of 4Ps participation on nutritional outcomes in the Philippines - Alyssa Villanueva; Valerie Gilbert Ulep; Rosela Agcaoili (Philippine Institute for Development Studies (PIDS), 2024)
Over the years, the Pantawid Pamilyang Pilipino Program (4Ps) has been at the forefront of the government's efforts to alleviate poverty and improve health and nutrition outcomes among the most vulnerable Filipino families. These programs, which offer financial assistance in return for complying with health, education, and nutrition-related requirements, have shown positive effects on children's nutritional outcomes. This study investigates how children's nutritional outcomes are affected by conditional cash transfers (i.e., 4Ps) in the Philippines. It aims to explore the role that the 4Ps play in the prevalence of stunting and wasting in children. By using the 2018-2019 Expanded National Nutrition Survey (ENNS) from the Food and Nutrition Research Institute, and through propensity score matching, the research assesses the probability that the poor and poorest households will take part in the 4Ps program. The study estimates the causal effect of 4Ps participation on a range of nutritional indicators, including weight-for-height, height-for-age, weight-for-height, and body mass index Z-scores, stunting, underweight, wasting, and severe stunting, by comparing matched groups and taking various covariates into account. The results highlight the need for a nuanced understanding of the program's effects as they show no significant improvement in children's nutritional status based on the program's impacts.
Keywords: 330; Pantawid Pamilyang Pilipino Program (4Ps); conditional cash transfers (CCTs); nutrition; Philippines